WAMS-Based SSR Damping Controller Design for FACTS Devices and Investigating Effects of Communication Delays - Mortaza Farsadi; Arash Ghasemi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Recent technological progresses in the wide-area measurement systems (WAMS) are realizing the centralized controls as a breakthrough for improving the power systems stability. The most challenging deficiency against WAMS technology is related to communication delays. If this latency is neglected, it can deteriorate the damping performance of closed loop control or even degrade the system stability. This paper investigates a conventional Wide Area Damping Controller (WADC) for a static synchronous series compensator (SSSC) to damp out the Sub-Synchronous Resonance (SSR) and also investigation of the destructive effect of time delay in remote feedback signal. A new optimization algorithm called teaching-learning-based- optimization (TLBO) algorithm has been implemented to normalize and optimize the parameters of the global SSR damping controller. The IEEE Second Benchmark Model is considered as the system under study and all simulations are carried out in MATLAB/SIMULINK environment.